2016
DOI: 10.2147/dmso.s95247
|View full text |Cite
|
Sign up to set email alerts
|

eHealth technologies to support nutrition and physical activity behaviors in diabetes self-management

Abstract: Diabetes is a chronic, complex condition requiring sound knowledge and self-management skills to optimize glycemic control and health outcomes. Dietary intake and physical activity are key diabetes self-management (DSM) behaviors that require tailored education and support. Electronic health (eHealth) technologies have a demonstrated potential for assisting individuals with DSM behaviors. This review provides examples of technologies used to support nutrition and physical activity behaviors in the context of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
79
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(82 citation statements)
references
References 79 publications
2
79
0
1
Order By: Relevance
“…This trend has been documented in the fields of medicine [2], nursing [3], psychology [4], kinesiology [5], nutrition [6], and for multiple health concerns and diseases [1]. …”
Section: Introductionmentioning
confidence: 99%
“…This trend has been documented in the fields of medicine [2], nursing [3], psychology [4], kinesiology [5], nutrition [6], and for multiple health concerns and diseases [1]. …”
Section: Introductionmentioning
confidence: 99%
“…In 2014, about 422 million people worldwide have been diagnosed with diabetes that 10 percent of them with had Type I diabetes [5]. The disease affects one person from every 400 to 600 children [6] and 3-4 percent increases each year in European children [7].…”
Section: Editorialmentioning
confidence: 99%
“…Delivering lifestyle interventions can be a particular challenge for women with young children. Electronic health (eHealth) technologies provide a potential solution for supporting diabetes self-management [ 17 ] Interventions delivered using eHealth technologies have the potential to address common barriers faced by postpartum women, such as time and competing demands, by providing a flexible method of delivery that promotes sustained engagement and self-monitoring [ 18 , 19 ]. A systematic review found that eHealth interventions had a positive effect on weight management compared to control among postpartum women [ 20 ].…”
Section: Introductionmentioning
confidence: 99%